Sliding wear of microalloyed wheel steel and high-strength rail steel under very high normal load at room temperature and under mild normal load at room and elevated temperatures - Xavier, Leonardo Medeiros (2024)
The sliding of the wheel flange against the rail gauge corner is critical in rail transportation, particularly in sharp curves where this sliding prevents derailment of the vehicle. However, this comes at the cost of severe wear due to the elevated stresses and temperatures developed in the contact. Understanding the wear behavior of this tribosystem is crucial in reducing the increased costs associated with the maintenance of the wheels and rails. To provide valuable insights into the wear mechanisms of wheel and rail steels in high stress and high-temperature applications, this work investigated, through two different studies, the evolution of tribologically transformed layers (TTLs) beneath the wear tracks, originated from the sliding of microalloyed wheel steel against high-strength rail steel; as well as the influence of temperature on friction and wear mechanisms. The first study focused on the formation and evolution of TTLs beneath the contact. Ring-on-disc sliding wear tests were carried out in air, at room temperature, and under a very high normal load (8 kN), with AAR Class D wheel steel discs sliding against AREMA TR68 high-strength rail steel rings, over increasing sliding distances and at two sliding speeds. The results showed that the high-load tests produced TTLs with thicknesses comparable to those observed in serviced wheels flanges and rails, with TTLs over 100 µm thick formed even at short sliding distances (6 m). Significant subsurface hardening was observed on discs and rings at different sliding distances, with seizure occurring at 132 m, marked by a sudden increase in temperature and friction. The second study explored the role of temperature in the friction and wear of the aforementioned materials through pin-on-disc sliding wear tests in air, under a normal load of 24.6 N, and at three temperatures: 20 °C, 400 °C and 700 °C. These tests aimed to elucidate the effects of oxidation, thermal softening, and phase transformations on wear mechanisms. The results indicate that the coefficient of friction (COF) and wear rates vary significantly with temperature. At 400 °C, the lowest COFs were observed, as well as the lowest wear rate for the pins (rail), attributed to the formation of an oxide layer that mitigates asperity adhesion. At 700 °C, thermal softening due to decarburization of an upper layer immediately below the surface led to a significant increase in the wear rates on the discs (wheel), suggesting a transition in the wear regime between 400 °C and 700 °C.